Novel Strategies for Malaria Vaccine Design - Frimpong, Augustina; Kusi, Kwadwo Asamoah; Ofori, Michael Fokuo; Ndifon, Wilfred (Frontiers in Immunology, 2018)
The quest for a licensed effective vaccine against malaria remains a global priority. Even though other vaccine design strategies have been successful for some viral and bacterial pathogens, little success has been achieved for Plasmodium falciparum, which causes the deadliest form of malaria due to its diversity and ability to evade host immune responses. Nevertheless, recent advances in vaccinology through high throughput discovery of immune correlates of protection, lymphocyte repertoire sequencing and structural design of immunogens, provide a comprehensive approach to identifying and designing a highly efficacious vaccine for malaria. In this review, we discuss novel vaccine approaches that can be employed in malaria vaccine design.